Flipped classroom in university-level mathematics: A decade of research trends and impact - Amirul Aizad, Ahmad Fuad; Ashraff, Ruslan; Anam, .; Abdullahi, Mujahid; Hadejia, Yunusa Aliyu (UPSI Press, 2026)
This bibliometric analysis investigates the adoption and development of the flipped classroom approach in university mathematics education using 165 Scopus-indexed journal articles published between 2014 and 2024. The research, conducted using Biblioshiny in R, examines publication trends, key contributors, and thematic patterns via co-citation networks and keyword mapping. Results demonstrate a steady increase in research output, particularly subsequent to 2020, driven by the shift toward blended and online learning. Dominant themes include student engagement, digital learning tools, and curriculum design, with an emerging emphasis on artificial intelligence and adaptive learning technologies. Citation analysis identifies foundational studies but highlights critical research gaps, including the need for standardized assessment frameworks, evaluation of long-term learning outcomes, and broader implementation across diverse mathematical subfields. This study provides a structured overview of the field and identifies directions for future inquiry, supporting educators and policymakers in advancing evidence-based teaching strategies in university-level Mathematics.